Mechanical Aspects of Deformation-Induced Surface Roughening in the Presence of Inclusions in a Subsurface Layer. Numerical Modeling - Romanova, Varvara; Dymnich, Ekaterina; Balokhonov, Ruslan; Zinovieva, Olga (Frontiers in Mechanical Engineering, 2020)
The mechanical aspects of deformation-induced surface roughening inherent in microstructural inhomogeneity are studied numerically using single inclusion models. Three-dimensional finite-element calculations of uniaxial tension are performed for a set of single inclusion models where a cubic-shaped inclusion is embedded into a homogeneous matrix. The inclusion-to-surface distance, tilt angle about the axis of tension, and the ratio between the matrix and inclusion elastic-plastic properties are varied in different combinations to study the effects which these parameters have on the development of out-of-plane surface displacements under uniaxial tension. It has been shown that all stress and strain tensor components in the vicinity of inclusions take on nonzero values, including those directed across the load axis. Thus, the free surface becomes rough under the action of internal forces originated from the inhomogeneous stress-strain fields. Some illustrative examples of surface roughening under uniaxial tension are shown for multiple ellipsoidal inclusions periodically arranged in a subsurface layer of an elastic-plastic material.